Beyond the human pen: The role of artificial intelligence in literary creation - Ali, Elsadig; Kottaparamban, Musadhique; Ahmed, Fawzi; Usmani, Saima; Hamd, Muna; Ibrahim, Mohammed; Hamed, Sarah (Research Journal in Advanced Humanities, 2025)
Artificial Intelligence (AI) is increasingly shaping the landscape of literary creation, offering new possibilities for writing that engage with, extend, and sometimes challenge traditional human literary practices. This study examines the multifaceted role of AI in literature, focusing on its impact on authorship, creativity, and the creation of literary texts. It evaluates AI-generated works on style, coherence, and literary merit, examining how these texts interact with human imagination and cultural expectations. It highlights the potential for AI to inspire writers, generate new narrative strategies, and increase the boundaries of literary experimentation, while also raising critical concerns about authenticity, artistic value, and the ethical implications of machine-assisted writing. Through comparative analysis and stylistic evaluation, the research investigates how AI influences literary expression, allowing the creation of texts that are sometimes indistinguishable from human writing in tone and style. The study suggests that AI is not merely a tool but an active participant in literary processes, capable of enriching creative practice while prompting reflection on the evolving relationship between human authors and intelligent systems. Empirical findings revealed that AI-driven content generation dominates article writing (85.1%) and copywriting (47.8%), while human-authored texts exhibit higher idea density (0.5) than AI-generated texts (0.4), underscoring stylistic and cognitive distinctions. It emphasizes the significance of integrating AI thoughtfully into literary creation, balancing innovation with the preservation of cultural and imaginative contributions that remain uniquely human.